Effect of sulfuric acid concentration on corrosion behavior of Al0.1CoCrFeNi high-entropy alloy. (February 2022) - Sun, Yipu; Lan, Aidong; Wang, Zhong; Zhang, Min; Qiao, Junwei
Abstract: The influence of H2 SO4 solution concentration on the corrosion behavior of as-cast Al0.1 CoCrFeNi high-entropy alloys (HEAs) is investigated. The potentiodynamic polarization curves of the Al0.1 CoCrFeNi HEA exhibit excellent corrosion resistance and a wide passive region (ΔE > 1150 mV) in acid solutions. The samples show a spontaneous passivation behavior in low-concentration (0.1, 0.2 and 0.3 M) and two anodic active–passive peaks in high-concentration (0.5 and 1.0 M) H2 SO4 solutions. The morphology investigation by scanning electron microscopy suggests that selective corrosion is initiated from the inter-dendrite regions. The X-ray photoelectron spectroscopy results demonstrate that the observed passive behavior variation is associated with chemical composition change of the passive films. Highlights: Effect of acid concentration on Al0.1 CoCrFeNi HEA corrosion behavior was studied. The Al0.1 CoCrFeNi HEA exhibits an extensive passive region in acidic solutions. Element contents differ in the passivation films formed under different potentials.